A comparative quantitative assessment of 3D-printed PEKK and PEEK thin meshes in customized alveolar bone augmentation - Xin-Rui Zhu; Chang Chen; Yun-Wei Hua; Xiao-Ying Xu; Ping Song; Rui-Yong Wang; Chen-Xi Wang (BMC, 2024)
Abstract Objective Customized nonabsorbable membranes are widely used in severe alveolar bone defects and provide sufficient and precise regenerated bone tissue for subsequent dental implant placement. Although 3D-printed polyetheretherketone (PEEK) meshes have confirmed successful use in clinical cases, the performance of a PEEK mesh is not satisfactory. Compared with PEEK, polyetherketoneketone (PEKK) has better mechanical and processing properties. However, whether PEKK is suitable for making customized membranes remains unclear. The objectives of this study were (1) to evaluate the printing precision, surface characteristics, mechanical characteristics and biocompatibility of the PEKK mesh and (2) to compare the properties of the PEKK and PEEK meshes. Materials and methods Both PEKK and PEEK meshes were designed and manufactured via additive manufacturing technology combined with computer-aided design (CAD). The printing precision was evaluated with a high-resolution extraoral scanner. The surface characteristics were evaluated with a contact angle system and three-dimensional optical microscopy. The mechanical characteristics were evaluated via three-point bending tests and tensile tests. The biocompatibility was evaluated with a CCK-8 assay, live/dead viability assay and qRT-PCT. Results Compared with the PEEK mesh, the PEKK mesh exhibited better control in terms of the thickness and aperture area. Both the PEKK mesh and the PEEK mesh had a hydrophobic surface, but the PEKK mesh had a smoother surface. Compared with the PEEK mesh, the PEKK mesh has better compression and tensile properties. Both the PEKK mesh and the PEEK mesh had good biocompatibility. The proliferation of cells on the PEKK mesh was slightly lower than that on the PEEK mesh. Conclusions Compared with PEEK mesh, PEKK mesh has greater printing accuracy, smoother surfaces, better mechanical properties and similar biocompatibility and is expected to be used in the production of customized barrier membranes for the augmentation of severe bone defects. To ensure the stability of the mesh for clinical application, it is best to control the aperture diameter of the PEKK mesh to less than 2 mm with a thickness of 0.2 μm.